Impact of diaper change frequency on preterm infants' vital sign stability and skin health: A RCT. (January 2022) - Brandon, Debra H.; Hatch, Daniel; Barnes, Angel; Vance, Ashlee J.; Harney, Jane; Voigtman, Barbara; Younge, Noelle
Abstract: Background: Bundling nurse caregiving interventions are promoted to minimize infant stress. Purpose: To evaluate impact of bundled nursing care and diaper change frequency on vital sign stability and skin health of preterm infants born ≤32 weeks gestation. Method: Stable preterm infants on a 3-hour feeding schedule were randomly assigned to 3- vs. 6-hour diaper changes. Diapers were changed prior to 6 h if stool was present. Direct observation of bundled care events (BCE) identify caregiving activities during each BCE. Skin pH, transepidermal water loss (TEWL), and neonatal skin condition scores (NSCS) were obtained. Vital sign data (HR, RR, O2 saturation) was downloaded from bedside monitors. Results: Forty-six infants contributed to 605 BCEs. BCEs lasted on average 28 min and included nine different activities (e.g., vital signs, feeding). Significant increases in heart rate during BCEs occurred in approximately half of the observations. Among observations with a diaper change increases in heart rate during diapering occurred in over 74% of observations Infants who were awake at the beginning of BCEs had 48% lower odds of having a change in heart rate than infants who were sleeping ( p  = .02). There were no group differences (3- vs. 6-hour diaper change) in skin health outcomes (TEWL, pH, NSCS). Conclusion: Reducing diaper change frequency without stool present should be considered to minimize caregiving stress in preterm infants. Additional research should evaluate the intrusiveness and clusters of activities that significantly impact physiologic stability to better individualize the timing of routine yet intrusive activities. Clinicaltrials.gov registry # NCT03370757 Highlights: Significant increases in heart rate occurred over 74% of the time during bundled care with a diaper change. Less frequent diaper changes do not affect buttock transepidermal water loss or skin pH in stable premature infants. Significant changes in heart rate are less likely to occur if an infant is awake at the beginning of bundled caregiving.